Intranasal cerium oxide nanoparticles improves locomotor activity and reduces oxidative stress and neuroinflammation in haloperidol-induced parkinsonism in rats - Mohammad,; Khan, Urooj Ahmed; Warsi, Musarrat Husain; Alkreathy, Huda Mohammed; Karim, Shahid; Jain, Gaurav Kumar; Ali, Asgar (Frontiers in Pharmacology, 2023)
Introduction: Cerium oxide nanoparticles (CONPs) have been investigated for their therapeutic potential in Parkinson’s disease (PD) due to their potent and regenerative antioxidant activity. In the present study, CONPs were used to ameliorate the oxidative stress caused by free radicals in haloperidol-induced PD in rats following intranasal administration. Method: The antioxidant potential of the CONPs was evaluated in vitro using ferric reducing antioxidant power (FRAP) assay. The penetration and local toxicity of the CONPs was evaluated ex-vivo using goat nasal mucosa. The acute local toxicity of intranasal CONPs was also studied in rat. Gamma scintigraphy was used to assess the targeted brain delivery of CONPs. Acute toxicity studies were performed in rats to demonstrate safety of intranasal CONPs. Further, open field test, pole test, biochemical estimations and brain histopathology was performed to evaluate efficacy of intranasal CONPs in haloperidol-induced PD rat model. Results: The FRAP assay revealed highest antioxidant activity of prepared CONPs at a concentration of 25 μg/mL. Confocal microscopy showed deep and homogenous distribution of CONPs in the goat nasal mucus layers. No signs of irritation or injury were seen in goat nasal membrane when treated with optimized CONPs. Scintigraphy studies in rats showed targeted brain delivery of intranasal CONPs and acute toxicity study demonstrated safety. The results of open field and pole test showed highly significant (p < 0.001) improvement in locomotor activity of rats treated with intranasal CONPs compared to untreated rats. Further, brain histopathology of treatment group rats showed reduced neurodegeneration with presence of more live cells. The amount of thiobarbituric acid reactive substances (TBARS) was reduced significantly, whereas the levels of catalase (CAT), superoxide dismutase (SOD), and GSH were increased significantly, while amounts of interleukin-6 (IL-6) and tumour necrosis factor-alpha (TNF-α) showed significant reduction after intranasal administration of CONPs. Also, the intranasal CONPs, significantly high (p < 0.001) dopamine concentration (13.93 ± 0.85 ng/mg protein) as compared to haloperidol-induced control rats (5.76 ± 0.70 ng/mg protein). Conclusion: The overall results concluded that the intranasal CONPs could be safe and effective therapeutics for the management of PD.